HORMONAL AND ULTRASOUND PARAMETERS OF THE UTERUS AND APPENDAGES IN ADOLESCENT GIRLS BORN PRETERM - Светлана Ивановна Елгина; Елена Николаевна Никулина (The Publishing House Medicine and Enlightenment, 2017)
Objective - to estimate the ovarian reserve (hormones and ultrasound parameters of the uterus and appendages) in adolescent girls born preterm compared to full-term ones. Materials and methods. Two hundreds adolescent girls aged 15-16 years born preterm and full-term were studied with laboratory, ultrasound, statistical methods. Results. Statistically significant differences in hormonal indicators of ovarian reserve of adolescent girls born preterm compared to full-term girls: estradiol level (p = 0.0001), Anti-Mullerian hormone (p = 0.0001), inhibin B (p = 0.0001) is lower in girls born as premature infants, and FSH (p = 0.0001) and luteinizing hormones (p = 0.0001) have higher levels. Ultrasonic parameters of the uterus and appendages are also different. Adolescent girls born preterm compared to full-term ones have a longer cervix, the smaller size of M-ECHO, the length and width of the uterus, smaller ovaries and fewer follicles in them. Conclusion. The ovarian reserve in adolescent girls born preterm compared to full-term girls was estimated. Miscarriage makes a change in the formation of the reproductive system in postnatal period. The differences specified in the parameters of ovarian reserve in adolescent girls born preterm show the immaturity and hypofunction of the reproductive system.